Comparing neoadjuvant nab-paclitaxel vs paclitaxel both followed by anthracycline regimens in women with ERBB2/ HER2-negative breast cancer-the evaluating treatment with neoadjuvant abraxane (ETNA) trial a randomized phase 3 clinical trial - Gianni, L.; Mansutti, M.; Anton, A.; Calvo, L.; Bisagni, G.; Bermejo, B.; Semiglazov, V.; Thill, M.; Chacon, J.; Chan, Arlene; Morales, S.; Alvarez, I.; et al. (2018)
© 2018 American Medical Association. All rights reserved. IMPORTANCE Studies of neoadjuvant chemotherapy regimens using anthracyclines followed by taxanes have reported a doubling of pathological complete remission (pCR) rates compared with anthracycline-based regimens alone. A reverse sequence did not reduce activity. Nab-paclitaxel is an albumin-bound nanoparticle of paclitaxel that allows for safe infusion without premedication, and its use led to a significantly higher rate of pCR in the GeparSepto trial. OBJECTIVE To determine whether nab-paclitaxel improves the outcomes of early and locally advanced human epidermal growth factor receptor 2 (ERBB2/HER2)-negative breast cancer compared with paclitaxel when delivered in a neoadjuvant setting. DESIGN, SETTING, AND PARTICIPANTS In this multicenter, open-label study, in collaboration with Grupo Español de Investigación en Cáncer de Mama (GEICAM) and Breast Cancer Research Center-Western Australia (BCRC-WA), patients with newly diagnosed and centrally confirmed ERBB2/HER2-negative breast cancer were recruited. Participants were randomly allocated to paclitaxel, 90 mg/m 2 (349 patients), or nab-paclitaxel, 125 mg/m 2 (346 patients). The 2 drugs were given on weeks 1, 2, and 3 followed by 1 week of rest for 4 cycles before 4 cycles of an anthracycline regimen per investigator choice. MAIN OUTCOMES AND MEASURES The primary end point was the rate of pCR, defined as absence of invasive cells in the breast and axillary nodes (ie, ypT0/is ypN0) at the time of surgery. A secondary end point was to assess tolerability and safety of the 2 regimens. RESULTS From May 2013 to March 2015, 814 patients were registered to the study; 695 patients met central confirmation eligibility and were randomly allocated to receive either paclitaxel (349), or nab-paclitaxel (346) (median age, 50 years; range, 25-79 years). The intention-to-treat analysis of the primary end point pCR revealed that the improved pCR rate after nab-paclitaxel (22.5%) was not statistically significant compared with paclitaxel (18.6%; odds ratio [OR], 0.77; 95% CI, 0.52-1.13; P = .19). Overall, 38 of 335 patients (11.3%) 11.3% of patients had at least 1 serious adverse event in the paclitaxel arm and 54 of 337 patient (16.0%) in the nab-paclitaxel arm. Peripheral neuropathy of grade 3 or higher occurred in 6 of 335 patients (1.8%) and in 15 of 337 (4.5%), respectively. CONCLUSIONS AND RELEVANCE The improved rate of pCR after nab-paclitaxel was not statistically significant. The multivariate analysis revealed that tumor subtype (triple-negative vs luminal B-like) was the most significant factor (OR, 4.85; 95% CI, 3.28-7.18) influencing treatment outcome.